The criteria set by banks in financing the development of a project: a comparative study of 5 banks / Nurulain Kamarulekhsan - Kamarulekhsan, Nurulain (2010)
Project developers are the main players in the construction industry, which in the last 20 years has been growing rapidly in tandem with the national development. In fact, according to the Malaysian Industrial Classification (MIC) 1972, the construction sector is among the 10 fastest growing industries in Malaysia. Although the contribution of the developers is an indirect injection into the national economy, it is important to look into their requirements for financial assistance and difficulties in receiving progressive funding in the implementation of development projects. It is especially important to examine the case of large projects that involve big expenditure or high cost with the aim to maximize returns to project developers. Rarely do developers finance their projects with 100% of their own money because it is a difficult matter, except for firms, companies, and corporations with large and strong financial base. Usually, most developers turn to financial institutions, such as banks, for credit facilities or loans. However, this is not necessarily an ideal situation to expedite project development. Problems do accrue. Among the problems is delay in the disbursement of credits that will affect a development in the form of construction and completion delays or in an extreme case, project abandonment. The purpose of this Bachelor degree terminal project is to determine the causes of delay in disbursing credits by financial institutions to real estate developers. In order to identify the causes of delay, one set of survey forms will used to interview the selected financial institutions and the selected developers to obtain the necessary information to meet the research goal. The data obtained will be analyzed by using quantitative analysis method and the results discussed in a descriptive manner. In conclusion, the study is to show that the financial institutions concerned are measuring the progress of development projects in stages against a set of criteria and conditions to grant progressive funding to developers. It also hopes to show the delay factors which cause the developers unable to fulfill the requirements which have been fixed by banks. The study hopes to present some proposals to overcome delays in progressive disbursement of credit to avoid problems of delay in a real estate development.